2019
DOI: 10.4028/www.scientific.net/msf.944.303
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Cooling Phase Transformation Rule of 20CrMnTi Low-Carbon Alloy Steel

Abstract: Gear steel is a ferritic steel. In the rolling process, the ideal structure is ferrite + pearlite, and bainite or martensite is not expected. However, due to the high alloy content, the hardenability is good, and the bainite or martensite structure is very likely to be generated upon cooling after rolling. In this paper, phase transformation rules during continuous cooling of 20CrMnTi with and without deformation were studied to guide the avoidance of the appearance of bainite or martensite in steel. A combine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Han, X. et al [11] studied the grain evolution process of gear tooth surface with an optical microscope and studied the evolution of cementite particles and gear tooth microstructure during cold rotary forging. Li, L. et al [12] studied the transformation law of 20CrMnTi during continuous cooling and found that there were three transformation regions of ferrite-pearlite, bainite and martensite in 20CrMnTi during continuous cooling. When the cooling rate increased, the starting time and duration of ferrite transformation in the steel shortened, resulting in an increase in the hardness of 20CrMnTi steel.…”
Section: Introductionmentioning
confidence: 99%
“…Han, X. et al [11] studied the grain evolution process of gear tooth surface with an optical microscope and studied the evolution of cementite particles and gear tooth microstructure during cold rotary forging. Li, L. et al [12] studied the transformation law of 20CrMnTi during continuous cooling and found that there were three transformation regions of ferrite-pearlite, bainite and martensite in 20CrMnTi during continuous cooling. When the cooling rate increased, the starting time and duration of ferrite transformation in the steel shortened, resulting in an increase in the hardness of 20CrMnTi steel.…”
Section: Introductionmentioning
confidence: 99%